DOP72 Safety, tolerability and efficacy of anti-TL1A antibody PF-06480605 in treatment of ulcerative colitis: The open-label, multicentre, Phase 2a TUSCANY study. (15th January 2020) - Danese, S; Klopocka, M; Scherl, E J; Romatowski, J; Allegretti, J R; Peeva, E; Vincent, M S; Schoenbeck, U; Xi, L; Ye, Z; Hassan-Zahraee, M; Rath, N; et al.
Abstract: Background: Widespread disruption of the mucosal immune system is central to the pathogenesis of ulcerative colitis (UC). One component, tumour necrosis factor (TNF) α-like ligand 1A (TL1A), is upregulated at the site of active disease in UC. Treatment of preclinical rodent models with anti-TL1A antibodies decreases disease activity, highlighting their therapeutic potential for UC. PF-06480605 is a first-in-class fully human immunoglobulin G1 monoclonal antibody targeting TL1A. Methods: The Phase 2a, open-label, multicentre, single-arm TUSCANY study (NCT02840721) evaluated the safety, tolerability and efficacy of PF-06480605 in treatment of moderate to severe UC. Participants received 500 mg intravenous (IV) PF-06480605 every 2 weeks (Q2W) for a total of 7 doses, with a 14-week follow-up period. Primary safety and efficacy endpoints were incidence of treatment-emergent adverse events (TEAEs) and endoscopic improvement (EI) (Mayo endoscopic subscore [centrally read] of ≤1 without friability) at Week 14, respectively. Secondary efficacy endpoints included remission (total Mayo score ≤2, with no individual subscore >1) and endoscopic remission (Mayo endoscopic subscore = 0) at Week 14. Transcriptomic profiling on intestinal biopsies was performed. Results: Of the 50 participants who received PF-06480605, 42 completed the study. The majority were male (56.0%) and white (96.0%), with a mean age of 40.0 years and prior experience of anti-TNF inhibitors (72.0%). Pancolitis (48.0%) and left-sided colitis (32.0%) were the most common forms of UC at baseline. There were 109 TEAEs, of which 18 were treatment-related. Aside from worsening UC, the most common TEAE by system organ class was arthralgia, which occurred in 6 participants, and 1 was treatment-related. Treatment-emergent serious adverse events were reported in 3 participants, and considered treatment-related in 1 participant (Table 1). No malignancies or deaths were reported. At Week 14, statistically significant EI was observed in 38.2% of participants (Table 2). The proportions of participants achieving remission and endoscopic remission at Week 14 were 24.0% and 10.0%, respectively. Transcriptomic analyses demonstrated normalisation towards a non-inflamed transcriptome in participants with EI. Conclusion: PF-06480605 exhibited an acceptable safety and tolerability profile and statistically significant EI in participants with moderate to severe UC. These results warrant further evaluation in subsequent studies.